Peningkatan Kemampuan Penggunaan Alat Peraga bagi Guru melalui Bimbingan Teknis Supervisi di MI Yappi Ngrati - Yuriah (Jurnal Pendidikan Madrasah, 2022)
This study aims to determine the ability of teachers to use teaching aids through individual guidance activities at MI Yappi Ngrati for the 2020/2021 school year. This study uses an action research method that is carried out through two cycles. Each cycle includes planning, action, observation, and reflection activities. The results showed a significant increase in the ability of teachers to use teaching aids. This is evidenced by the results of the average percentage of teachers who reached 41.50% in the initial data increased to 60.66% in cycle 1 and increased to 72.33% in cycle 2. Individual guidance activities can be applied to madrasah teachers to improve their ability to manage and create a pleasant learning atmosphere through the use of teaching aids.